Role of organophosphorous pesticides and acetylcholine in breast carcinogenesis. (November 2021) - Calaf, Gloria M.
Abstract: Breast cancer is the leading cause of cancer-related death in women worldwide. Several studies have addressed the association between cancer in humans and agricultural pesticide exposure. Evidence indicates that exposure to organophosphorous pesticides such as parathion and malathion occurs as a result of occupational factors since they are extensively used to control insects. On the other hand, estrogens have been considered beneficial to the organism; however, epidemiological studies have pointed out an increased breast cancer risk in both humans and animals. Experimental female rat mammary gland cancer models were developed after exposure to parathion, malathion, eserine, an acetylcholinesterase inhibitor, and estrogen allowing the analysis of the signs of carcinogenicity as alteration of cell proliferation, receptor expression, genomic instability, and cell metabolism in vivo and in vitro . Thus, pesticides increased proliferative ducts followed by ductal carcinoma; and 17β-estradiol increased proliferative lobules followed by lobular carcinomas. The combination of both pesticides and either eserine or estrogen induced tumors with both types of structures followed by mammary gland tumors and metastasis to the lung and kidneys after 240 days of a 5-day treatment. Studies also showed that these pesticides and eserine decreased three to five times the acetylcholinesterase activity in the serum compared to controls whereas terminal end buds increased in number, being inhibited by atropine. Genomic instability was analyzed in such tissues (mp53, CYP1A2, c-myc, c-fos, ERα, M2R) and pesticides increased protein expression that was stimulated by estrogens but inhibited by atropine. Eserine also transformed the epithelium of the rat mammary gland in the presence of estrogen and increased the number of terminal end buds after treatment inducing mammary carcinomas. Then, enzymatic digestion of such structures gave rise to cells with increased DNA synthesis and induced anchorage independence. Thus, there were changes in the epithelium of the mammary gland influencing breast carcinogenesis. Furthermore, these substances and acetylcholine also showed the signs of carcinogenicity in vitro as cell proliferation, receptor expression (ERα, ErbB2, M2R), genomic instability (c-myc, mp53, ERα, M2R), and cell metabolism. A unique cellular model is also presented here based on the use of MCF-10 F, a non-tumorigenic cell line that represents a valuable clinically translatable experimental approach that identifies mechanistic links for pesticides and estrogen as suspect human carcinogenic agents.